PENGARUH PERGANTIAN AUDITOR, REPUTASI KAP, OPINI AUDIT, DAN KOMITE AUDIT DALAM AUDIT DELAY - Verawati, Ni Made Adhika; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2016)
Audit delay is the length of time the examination Completion As measured from the Closing Date Up to Date Company books Audited Financial Statements issued. Singer study aimed to investigate the influence of change of auditor review , reputation of KAP , audit opinion , Audit commite and against of Audit  delays . The study sample as many as 78 Manufacturing Company in Indonesia Stock Exchange ( BEI ) 2012-2014 With purposive sampling method. The analysis technique used is the Multiple Linear Regression . Research results show that ( 1 ) Audit auditor Substitution positive effect against the delay , ( 2 ) Reputation auditor Against negative influence audit delay , ( 3 ) Audit Opinion does not affect  audit dalay against, ( 4 ) audit committee does not affect audit delay Against.
Keywords: change of auditor , reputation of KAP , audit opinion, audit committees, audit delay